Electronic structures study of silicon, tin and their alloy - Tan, Eugene ZhiWei. (2009)
Efforts to improve the optical performance of the indirect bandgap semiconductor silicon (Si) has been a major subject of research in the field of silicon photonics due to the promising applications of silicon based light emitters and detectors for optical communication. A simulation on the silicon-tin alloy was done in the search for a more effective material for use in photonics. An understanding of the individual silicon and tin material is needed to deduce what are the effects of adding tin to silicon. Vienna ab initio Simulation Package (VASP), which employs first principles, was used to calculate the electronic parameters such as equilibrium lattice constant, band energies and effective mass of silicon and tin. The Luttinger parameters for silicon and tin were also calculated based on the results obtained from VASP. However, VASP was not able to provide accurate calculations for tin. Hence, the effective mass and Luttinger parameters of the silicon-tin alloy were not calculated. The short comings of the VASP were also highlighted as a result of this project.